Neoadjuvant Systemic Therapies in Bladder Cancer - Chu, Carissa E.; Iyer, Gopa; Bochner, Bernard H. (Frontiers in Urology, 2022)
Muscle-invasive bladder cancer (MIBC) is often framed as a systemic disease given the risk of occult metastases and clinical under-staging at the time of radical cystectomy. The current standard of care for non-metastatic MIBC combines a cisplatin-based neoadjuvant chemotherapy regimen followed by radical cystectomy, pelvic lymph node dissection, and urinary reconstruction. Other systemic therapies initially developed for the metastatic setting are being explored in the neoadjuvant space with favorable clinical outcomes. Immune checkpoint inhibitors targeting the programmed cell death-1/ligand-1 (PD-1/PD-L1) axis have demonstrated promising outcomes for cisplatin-ineligible patients in the neoadjuvant setting. Other novel targeted therapies under investigation in the perioperative setting include fibroblast growth factor receptor or FGFR inhibitors and antibody drug conjugates (enfortumab vedotin targeting Nectin-4 and sacituzumab govitecan targeting Trop-2). Non-chemotherapy-based treatments have the potential to expand the application of neoadjuvant therapy for many patients, particularly those who are cisplatin-ineligible due to comorbidities or who harbor chemotherapy-resistant tumors. The expansion of neoadjuvant therapy options also provides an opportunity to characterize mechanisms of tumor resistance and elucidate tumor biology with ongoing correlative studies.